Development of IoT-Based Lighting Installation Practicum Module - Shidiq, Ahmad Mukhaidir; Purwito, Purwito; Ruslan, Ruslan (Politeknik Negeri Ujung Pandang, 2021)
With the advancement of technology today, there is known to be an innovation that is the internet of things where electronic devices can be monitored and controlled remotely. For this reason, the practicum module of internet of things-based lighting installation as a medium of learning for students. The workings of the tool will be made using the PZEM-004T sensor as a sensor reading the current voltage, power, and energy used and ESP-32 as an additional module on the Arduino Mega so that data reading voltage, current and power can be sent using the internet network to the smartphone. In the smartphone application, we can also control to extinguish or turn on the lights.